To the problem of public management of financial and economic security of Ukraine in the conditions of the COVID-19 pandemic - Dobrovolska, Olena; Добровольська, Олена Володимирівна; Moskalenko, S.; Москаленко, С.; Kucher, G.; Кучер, Г.; Skoryk, H.; Скорик, Г.; Mudra, Y.; Мудра, Я. (Університет банківської справи, 2022)
The article identifies the main problems that arise in the public management of the financial and economic security of Ukraine in the context of the COVID-19 pandemic, the possible consequences of the pandemic in terms of impact on economic and national security. The objectives of the study are to study the impact of the coronavirus pandemic on the financial and economic system of Ukraine and the world economy, analysis of the threat of biological factors on the economic and national security of Ukraine. The subject of the study is the analysis of problems of public management of financial and economic security of Ukraine in the COVID-19 pandemic, which is a response to current issues for our country: economic stagnation, inflation, unresolved issues related to rising food prices and deteriorating geopolitical situation. The authors argue that the independence, stability, competitiveness of the national economy and financial and economic security of Ukraine depends primarily on ensuring the economic security of each of its regions. The authors of the article developed and substantiated the provision that public management of financial and economic security of Ukraine in the COVID-19 pandemic is associated with strengthening economic security of regions, which should be based on improving state regulation of economic growth by creating regulations of territorial and interregional planning aimed at supporting the real sector of the economy and the development of promising technologies that will be effective in the context of the COVID-19 pandemic. In the article the authors paid attention to the study of theoretical and practical importance of financial and economic security of Ukraine and effective public administration in this area, as an integral part of national security of our state. Визначено основні проблеми, які виникають у публічному управлінні фінансово-економічною безпекою України в умовах пандемії COVID-19, можливі наслідки пандемії в аспекті впливу на економічну та національну безпеку. Завдання дослідження — дослідження впливу пандемії коронавірусної інфекції на фінансово-економічну систему України та світову економіку, аналіз загрози біологічного фактора на економічну та національну безпеку України. Предмет дослідження — аналіз проблем публічного управління фінансово-економічною безпекою України в умовах пандемії COVID-19, що є відгуком на актуальні питання для нашої країни: стагнація економіки, інфляція, невирішені проблеми, пов'язані зі зростанням цін на продовольчі товари та погіршенням геополітичної ситуації. Авторами доведено думку про те, що незалежність, стійкість, конкурентоспроможність національної економіки та фінансово-економічна безпека України, залежить, насамперед, від забезпечення економічної безпеки кожного її регіону. У статті авторами розроблено та обґрунтовано положення про те, що публічне управління фінансово-економічною безпекою України в умовах пандемії COVID-19 пов’язано зі зміцненням економічної безпеки регіонів, яке повинно базуватися на вдосконаленні державного регулювання економічного зростання шляхом створення нормативно-правових актів територіального та міжрегіонального планування, спрямованих на підтримання реального сектора економіки та розвиток перспективних технологій, що будуть дієвими в умовах пандемії COVID-19. У статті автори приділили увагу дослідженню теоретичного та практичного значення фінансово-економічної безпеки України та ефективного публічного управління у цій сфері, як невід'ємної складової національної безпеки нашої держави.
До проблеми публічного управління фінансово-економічною безпекою України в умовах пандемії COVID-19
Keywords: national security; національна безпека; economic security; економічна безпека; public administration; публічне управління; financial security; фінансова безпека; COVID-19 pandemics; пандемії COVID-19